Diagnosing Early Cardiac Tamponade in Patient with JAK2+ Myeloproliferative Syndrome with Point of Care Ultrasound - Evan Cameron; Lawrence Istrail (POCUS Journal, 2021)
Point of care ultrasound (POCUS) is a diagnostic modality growing in popularity and use in medicine in both the acute and chronic management settings. Its utility lies in its non-invasive application, direct user interface, and portability, especially in handheld devices, allowing for quick assessment and triage. Herein is a case of POCUS diagnosing life threatening cardiac tamponade in a patient with a new diagnosis of JAK2+ myeloproliferative syndrome prompting urgent intervention with pericardiocentesis. This case illustrates the utility of POCUS through its ability to serve as a quick diagnostic tool that can hasten intervention for potentially life-threatening conditions.